Design of an ellipsoidal mirror assisted oblique plane microscopy - Liu, Yuzhe; Chen, Qiushu; Fei, Yiyan; Mi, Lan; Ma, Jiong (Frontiers in Physics, 2022)
Using one objective for excitation and detection simultaneously, oblique plane microscopy (OPM) provides a mounting-friendly approach for optical sectioning. Unfortunately, the original OPM has three major defects: the mechanical constraints when placing the objectives, the phase loss and the resulting anisotropy of the point spread function (PSF). In order to alleviate the above defects, an ellipsoidal mirror assisted oblique plane microscopy (EM-OPM) was proposed. By inserting an ellipsoidal mirror into the optical path to help collect the light beam, the problem of placing the objectives was solved. The numerical calculation results showed that EM-OPM can obtain higher relative light intensity and larger effective area of exit pupil than OPM when the tilt angle of the light sheet becomes larger. The imaging simulation results showed that EM-OPM effectively solves the problem of resolution reduction in the Y direction of OPM. In addition, optimization of the higher-order terms of the ellipsoidal mirror further improved the imaging ability of EM-OPM in large field of view (FOV).